Answers
Answered by
4
Hi Friend !!!
=================
![log_{4}(x + 3) - log_{4}(x - 1) = 2 - log_{4}(8) \\ \\ log_{4}( \frac{x + 3}{x - 1} ) = log_{4}(16) - log_{4}(8) \\ \\ log_{4}( \frac{x + 3}{x - 1} ) = log_{4}( \frac{16}{8} ) \\ \\ \frac{x + 3}{x - 1} = \frac{16}{8} log_{4}(x + 3) - log_{4}(x - 1) = 2 - log_{4}(8) \\ \\ log_{4}( \frac{x + 3}{x - 1} ) = log_{4}(16) - log_{4}(8) \\ \\ log_{4}( \frac{x + 3}{x - 1} ) = log_{4}( \frac{16}{8} ) \\ \\ \frac{x + 3}{x - 1} = \frac{16}{8}](https://tex.z-dn.net/?f=+log_%7B4%7D%28x+%2B+3%29+-+log_%7B4%7D%28x+-+1%29+%3D+2+-+log_%7B4%7D%288%29+%5C%5C+%5C%5C+log_%7B4%7D%28+%5Cfrac%7Bx+%2B+3%7D%7Bx+-+1%7D+%29+%3D+log_%7B4%7D%2816%29+-+log_%7B4%7D%288%29+%5C%5C+%5C%5C+log_%7B4%7D%28+%5Cfrac%7Bx+%2B+3%7D%7Bx+-+1%7D+%29+%3D+log_%7B4%7D%28+%5Cfrac%7B16%7D%7B8%7D+%29+%5C%5C+%5C%5C+%5Cfrac%7Bx+%2B+3%7D%7Bx+-+1%7D+%3D+%5Cfrac%7B16%7D%7B8%7D+)
8x+24 = 16x-16
24+16 = 16x-8x
40 = 8x
x = 5
Hope it helps u:-)
=================
8x+24 = 16x-16
24+16 = 16x-8x
40 = 8x
x = 5
Hope it helps u:-)
tejasri2:
iam a girl
Answered by
3
HELLO.......FRIEND!!
THE ANSWER IS HERE,
![= > \: log_{4}(x + 3) - log_{4}(x - 1) = 2 - log_{4}(8) = > \: log_{4}(x + 3) - log_{4}(x - 1) = 2 - log_{4}(8)](https://tex.z-dn.net/?f=+%3D++%26gt%3B++%5C%3A++log_%7B4%7D%28x+%2B+3%29++-++log_%7B4%7D%28x+-+1%29++%3D+2+-++log_%7B4%7D%288%29+)
![= > \: log_{4}( \frac{x + 3}{x - 1} ) = log_{4}(16) - log_{4}(8) = > \: log_{4}( \frac{x + 3}{x - 1} ) = log_{4}(16) - log_{4}(8)](https://tex.z-dn.net/?f=+%3D++%26gt%3B++%5C%3A++log_%7B4%7D%28+%5Cfrac%7Bx+%2B+3%7D%7Bx+-+1%7D+%29++%3D++log_%7B4%7D%2816%29++-++log_%7B4%7D%288%29+)
![= > \: log_{4}( \frac{x +3 }{x - 1} ) = log_{4}( \frac{16}{8} ) = > \: log_{4}( \frac{x +3 }{x - 1} ) = log_{4}( \frac{16}{8} )](https://tex.z-dn.net/?f=+%3D++%26gt%3B++%5C%3A++log_%7B4%7D%28+%5Cfrac%7Bx++%2B3+%7D%7Bx+-+1%7D+%29++%3D++log_%7B4%7D%28+%5Cfrac%7B16%7D%7B8%7D+%29+)
![= > \: \frac{x + 3}{x - 1} = \frac{16}{8} = 2 = > \: \frac{x + 3}{x - 1} = \frac{16}{8} = 2](https://tex.z-dn.net/?f=+%3D++%26gt%3B++%5C%3A++%5Cfrac%7Bx+%2B+3%7D%7Bx+-+1%7D++%3D++%5Cfrac%7B16%7D%7B8%7D++%3D+2)
![= > \: x + 3 = 2(x - 1) = > \: x + 3 = 2(x - 1)](https://tex.z-dn.net/?f=+%3D++%26gt%3B++%5C%3A+x+%2B+3+%3D+2%28x+-+1%29)
![= > \: x + 3 = 2x - 2 = > \: x + 3 = 2x - 2](https://tex.z-dn.net/?f=+%3D++%26gt%3B++%5C%3A+x+%2B+3+%3D+2x+-+2)
![= > \: \: x = 5 = > \: \: x = 5](https://tex.z-dn.net/?f=+%3D++%26gt%3B++%5C%3A++%5C%3A+x+%3D+5)
:-)Hope it helps u.
THE ANSWER IS HERE,
:-)Hope it helps u.
Similar questions
Social Sciences,
8 months ago
Math,
8 months ago
English,
8 months ago
Math,
1 year ago
Science,
1 year ago
English,
1 year ago
Math,
1 year ago
Computer Science,
1 year ago